An Analysis towards the Sustainability and Management of Waqf’s Properties in Malaysia with References to Johor - Yusoff, Rahmawati Mohd; Wahab, Norintan; Salleh, Rosnani Mohd; Atan, Siti Mariam; Baharudin, Mohammad Hidir (International Journal of Asian Social Science, 2021)
In Malaysia, waqf properties are held and put under the Department of Waqf, Zakat and Hajj (JAWHAR) at the federal level and under the State’s Islamic Religious Council (SIRC) of respective states for the state level. However, all these properties need a lot of funds to manage them, and issues arose on sustainability and management of these waqf properties. The research found no guidelines identified explicitly in any investigation or findings on the appropriate guideline to solve this issue. Therefore, this research seeks to determine the actual problems and the legal and procedural constraints relating to the management and sustainability of waqf properties, especially in Johor, that has never been available before. Hence, using qualitative research method, which include content analysis and interviews during field studies; this research aims to produce a comprehensive solution and possible sources of funding for the effective management and sustainability of waqf properties in Johor. It is determined that the issue of the insufficient fund, lack of proper planning by waqf Mutawalli, unregistered waqf land under SIRC, and outdated data are among the problems that become impediments to waqf development. Therefore, Mutawalli carried a big responsibility to ensure that the waqf properties shall be developed according to the classes agreed and affirmed by the donor (waqif), leading to positive consequences to Malaysia’s economic growth, especially in Johor.